Estudo das propriedades térmicas e luminescentes de Blendas de PC/PMMA dopadas com complexos de Er+3, Tb+3 e Eu+3 - Moura, Ana Paula de (2006)
In recent years, there has been a growing interest in the luminescent properties of rare earth metal containing polymers because of their potential use in fluorescence and laser systems related to their optical, electronic and magnetic properties. This work describes the investigation of the thermal and luminescent properties of the blends formed by bisphenol-A polycarbonate(PC) and poly(metyl methacrylate) (PMMA) doped with chelates of the kind, erbium(III) acetylacetonate [Er(acac)3(H2O)3], terbium(III) acetylacetonate [Tb(acac)3(H2O)3] and europium(III) thenoyltrifluoroacetonate [Eu(TTA)3(H2O)3]. The analysis of FTIR spectra indicated that the complexes were incorporated into the polymeric blend. Through the results obtained by thermogravimetry it is possible to verify that the blend pure 60/40 presents better thermal stability in comparison to the doped blend and the doped blends 20/80 have largar thermal stability when compared to the pure blends. By analyzing the SEM data it can be observed that the blend 20/80 and 60/40 doped with the complexes of [Er(acac)3(H2O)3], [Tb(acac)3(H2O)3] and [Eu(TTA)3(H2O)3] showed a better morphology than the pure blends. Based on the EDS analysis it is possible to verify that the complexes of [Er(acac)3(H2O)3], [Tb(acac)3(H2O)3]l and [Eu(TTA)3(H2O)3]. Were homogeneously distributed in the surface of the blends 60/40 and 20/80. The analysis of the [Er(acac)3(H2O)3] doped blends by spectroscopy of luminescence emission for blend doped with [Er(acac)3(H2O)3] demonstrated band in 1553nm corresponding to the transition 4I13/2→ 4I15/2 characteristic of Er+3. The samples doped with Eu+3 showed the presence of characteristic bands of the europium(III) due to the transition 5D0 →7Fj(J=0, 1, 2, 3, 4, 5 e 6), and the sample doped with terbium(III) showed characteristic bands corresponding the transition 5D4 →7Fj(J= 3, 4, 5 e 6). Results of Tb+3 lifetime showed high values for the blends 20/80 and 60/40 at low cncentration. Blends 20/80 doped with [Eu(TTA)3(H2O)3] presented values of lifetime and quantum efficiency larger than the blend 60/40 doped in all the concentrations and the doped blends showed larger values than the pure complexes.